PERANAN PEMERINTAH KECAMATAN DALAM MENINGKATKAN PENDIDIKAN (Suatu Studi Terhadap UPTD Kecamatan Loloda Kabupaten Halmahera Barat) - PURA, OLIFIA (JURNAL ADMINISTRASI PUBLIK, 2013)
ABSTRACT : Olifia temple under the guidance of Drs. M.S. Pangkey, M.Si as Main Supervisor and Drs. A.J. Rorong, M.Si as Supervising Companion, with Thesis Title: "The Role of Governmen in Improving Education District " A Study Of UPTD West Halmahera District Lolod. In this study, there are some issues that are a barrier to improving the quality and the quality of education, especially in the West Halmahera District Loloda. The problem - the problem in question is the lack of understanding of the education system so that the responsibility for improving education in both government and the community is very low. Another problem as well as the education budget, curriculum, facilities, teachers, and other factors such as the principles of governance. All of this has not been implemented by regulations. The method used in this research is qualitative method using qualitative descriptive format. This research was conducted in the District of West Halmahera Loloda particularly in the government's efforts to improve the quality of education through UPTD. To get the expected results, then surely researchers needed a source or informant, by him that the researcher can determine the informants through a sample taken from the part of the population.Research variables consist of the independent variables and the dependent variable. Independent Variable is a role of government, while the Dependent Variable is improving education. The next step in this research using the instrument observation data collection, interviews, and through questionnaires. This study has the objective is to gain an overview of the role of government in improving education, which is expected to also get the benefit. The benefits of this research are theoretical benefits and practical benefits. Based on the results of the research can be judged that the government's role in improving education in the sub-districts of West Halmahera Loloda can work well although there are still many obstacles in the field and also the limitation of infrastructure of education, so I can say that the success of the government's role in running the school district has been running well although not quite